Periodic Oscillation Analysis for a Coupled FHN Network Model with Delays - Yuanhua Lin (Abstract and Applied Analysis)
The existence of periodic oscillation for a coupled FHN neural system with delays is investigated. Some criteria to determine the oscillations are given. Simple and practical criteria for selecting the parameters in this network are provided. Some examples are also presented to illustrate the result.